Contribution of cytochrome P450 isoforms to gliquidone metabolism in rats and human. (March 2014) - He, Fang; Li, Yun; Zeng, Caiwen; Xia, Chunhua; Xiong, Yuqing; Zhang, Hong; Huang, Shibo; Liu, Mingyi
Abstract 1. <?ri?>Gliquidone, a second generation sulfonylurea, is a widely used oral antidiabetic drug. Due to the differences in its rate of metabolism, gliquidone shows inter-subject variability in pharmacokinetic and pharmacodynamic profiles. 2. <?ri?>Cytochrome P450 (CYP450) isoforms are involved in the metabolism of a majority of drugs in clinical use and plays a significant role in reducing possible drug interactions. This research aimed to systematically study the contribution of various human CYP450 isoforms to gliquidone metabolism in vitro in rats and human. 3. <?ri?>In rat liver microsomes, gliquidone was metabolized mainly by the most abundant CYP2C. The other isoforms involved in the metabolism included CYP3A, CYP2D, CYP1A and CYP2E. 4. <?ri?>Further investigation of rat recombinant enzymes showed that CYP3A1 and CYP2C11 played a major role in gliquidone metabolism in vitro, while CYP2D1, CYP1A2 and CYP2E1 were also involved. 5. <?ri?>But the metabolism of gliquidone in the human liver microsomes was mainly mediated by CYP3A4. The other isoforms involved in this process were CYP2C9, CYP2C19 and CYP2D6. 6. <?ri?>The further study of human recombinant enzymes demonstrated that CYP3A4 was the principal isoform enzyme for the metabolism of gliquidone. The intrinsic clearance (Vmax/Km) of CYP3A4 during gliquidone metabolism was 3–12 times greater than that of other CYP450 isoforms including CYP2C9, CYP2D6 and CYP2C19. 7. <?ri?>These findings may assist in valuable prediction of potential interactions of gliquidone with other drugs that are CYP3A4 inhibitors or inducers and help to design more efficacious and safer pharmacotherapy for patients of diabetes mellitus.